The Meaning of Smoothing in Bima Language: A Study of Natural Semantic Metalanguage - Adawiyah, Rabiyatul (JOLLT Journal of Languages and Language Teaching, 2024)
Bima language verbs constitute one of the primary and complex word classes, pivotal in speech for their ability to determine the presence of arguments and assign semantic roles to each accompanying argument. This research aims to elucidate the configuration of meaning and explication of the verb ’refine’ in the Bima language. The data source comprises oral data collected from native speakers in Bima Regency, West Southeast Nusa. Data collection employed the listening method and note-taking techniques. The analysis utilized the Natural Semantic Metalanguage Theory (NSM), applying the equivalent method to analyze semantic structures and meaning components, and the distribution method to examine semantic roles. The findings reveal that the verbs in the Bima lexicon associated with ’refine’ are categorized as action verbs, exhibiting exponents of incompositional polysemy such as ’doing’ and ’happening’. This indicates that while the verb ’refine’ maintains a consistent core meaning, it encompasses specific nuances critical for accurate language use. The verb ’refine’ in Bima is mapped to several semantic domains: entity, process, tool, and result. It encompasses a range of meanings expressed by the lexicons: Soro (shove), kampao (smooth), ramba (sharpen), goso, soso (rub), kaniu (smooth), saruncu (to grind), pana`a (chewing), khasbi (pounding), kiru (crushing), gili (grinding), ndina (stomping), ledi (working), and mbaju (pounding). This research represents the first comprehensive study of the ’refine’ verb in the Bima language, providing crucial insights into its semantic structure and usage.